Academic Resilience Viewed from The Perspective of Emotional Regulation and Parental Support - Nurul Ilmiyah; Laurensius Laka (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
Poor academic resilience could lead to increased stress, decreased motivation to learn, difficulties in overcoming academic challenges, and burnout, which could ultimately result in a risk of dropping out of school. This study aimed to analyze the influence of emotion regulation and parental support on students' academic resilience. The research was conducted at State Vocational High School 1 Purwosari, targeting students in the RPL, APHP, and Mechatronics departments. The study involved a sample of 191 students selected using proportionate random sampling. Data were collected through questionnaires, and hypothesis testing was carried out using multiple regression analysis. The results showed that each independent variable (emotion regulation and parental support) had a partial significant effect on academic resilience (Sig.t = p < 0.05). Likewise, both independent variables simultaneously also had a significant effect on students' academic resilience (Sig.F = p < 0.05). Thus, both partially and simultaneously, all proposed hypotheses were proven to be accepted. Keywords: Academic resilience, emotion regulation, parental support